Preliminary investigation of growth and antimicrobial production by streptomyces polyantibioticus : from shake flask to stirred tank bioreactor - Matongo, Tarisayi Martin (Centre for Bioprocess Engineering Research, 2016)
Resistance to antibiotics by microbial pathogens continues to be a major global health problem. Treatment of bacterial infections is becoming increasingly complex and expensive. Tuberculosis (TB), caused by Mycobacterium tuberculosis infection, is affected by antibiotic resistance. In South Africa, the Western Province is the worst affected, with an increasing incidence of both multi-drug resistant (MDR) and extensively drug resistant (XDR) strains of M. tuberculosis. Both resistant forms of TB increase the length of treatment to almost 24 months and cost by as much as 1400 times that of regular anti-tubercular chemotherapy. A potential solution to this problem is the discovery of new drugs, which can be obtained from natural sources. Actinomycetes are good sources of these drugs, with over 45% of current medicines derived from these bacteria. The actinobacterium Streptomyces polyantibioticus SPRT (SPRT) was locally isolated and first described by Le Roes (2006). It has been shown to produce bioactive molecules active against a range of bacteria, including compounds (drugs) that have anti-tubercular properties. One of the anti-tubercular molecules was identified as 2,5-diphenyloxazole (DPO). DPO is currently used as a component of scintillation fluid for its luminescent properties and is synthesised chemically in industry. SPRT is the only reported biological source of DPO, it is however not yet produced commercially via a biological route. The present study was performed to inform future process development of DPO production from SPRT. An investigation into the growth and production of antimicrobial compounds from submerged cultures of SPRT in shake flasks, and scale-up of the process into a laboratory stirred tank bioreactor (STR) was done in the present study. The work focused on obtaining growth kinetics and suitable operating conditions for cultivation. Characterisation of the growth profile of SPRT and determination of the kinetic growth parameters was carried out. Additionally, the antimicrobial production phases, and factors influencing their production was investigated. It was determined that the most reliable method of measuring biomass concentration was by dry cell gravimetric measurement of whole shake flasks following vacuum filtration, as it best suited the non-homogenous filamentous nature of SPRT.